A Review of Posttraumatic Bowel Injuries in Ibadan. (17th August 2011) - Dongo, A. E.; Kesieme, E. B.; Irabor, D. O.; Ladipo, J. K.
Abstract : Background . Bowel injuries are a leading cause of morbidity and mortality following trauma. Evaluating patients who sustained abdominal trauma with bowel injury may pose a significant diagnostic challenge to the surgeon. Prompt recognition and timely intervention is necessary to improve outcome. Aim . This study was undertaken to evaluate treatment and outcome of patients with bowel trauma. Methods . A 5-year retrospective study of all patients presenting with abdominal trauma requiring surgical intervention seen in the UCH Ibadan, Nigeria was undertaken. Results . There were 71 patients (59 males and 12 females). The majority of cases (70%) occurred between the 3rd and 5th decades of life. Some 37 patients (52%) sustained blunt abdominal injury, while 34 patients (48%) sustained penetrating abdominal injury. There were 27 patients with bowel injuries (38%). Isolated bowel injuries occurred in 19 patients (27%). The most common surgical operation performed was simple closure. There were 3 deaths in patients with bowel injuries. Conclusion . Most cases of bowel injury can be managed by simple closure, a technique that is not so technically demanding for surgeons in less-developed countries. This study has also incidentally identified a "rule of six" for patients with bowel injuries and abdominal trauma.